Robust control of nonlinear time-delay systems - Antoniades, Charalambos; Christofides, Panagiotis D. (Zielona Góra: Uniwersytet Zielonogórski)
This paper focuses on single-input single-output nonlinear differential difference equation (DDE) systems with uncertain variables. For such systems, a general methodology is developed for the synthesis of robust nonlinear state feedback controllers that guarantee boundedness of the states and ensure that the ultimate discrepancy between the output and the external reference input in the closed-loop system can be made arbitrarily small by an appropriate choice of controller parameters.
Keywords: model uncertainty; time-delays; nonlinear robust control; fluidized catalytic cracker